Analisis determinan kinerja Bank Pembiayaan Rakyat Syariah di Indonesia (pendekatan Direct Error Correction Model) - Jihad Lukis Panjawa; Mahrus Lutfi Adi Kurniawan; Lak lak Nazhat El Hasanah (Faculty of Economics, Universitas Islam Indonesia, 2017)
AbstractIslamic banking is emerging as a breakthrough and an alternative to conventional banking. The shariah-compliant financial services industry is currently at a growing stage compared to the advanced conventional financial services industry. The presence of the Shariah People Financing Bank also contributed to the economy as a credit channeling institution and it is expected that the wheels of the economy will spin faster and give a positive effect to the national economy. This study aims to analyze the influence of internal and external factors on the performance of Sharia Bank Financing in Indonesia Year 2011-2016. The analytical tool used in this research is the Error Corretion Model (ECM) which assumes the existence of a long-run equilibrium relationship between two or more economic variables, however in the short term that occurs is disequilibrium. With the error correction mechanism, a proportion of disequilibrium in a period is corrected in the next period. The results of this study indicate in the short term, internal factors represented by CAR and BOPO, and external factors are represented Exchange Rate and Inflation does not affect the Return On Asset Bank Syariah Rakyat Rakyat. In the long run CAR, BOPO and Kurs have a significant effect, while inflation does not significantly affect Return On Asset of Rural Bank of Sharia Liabilities.